PENGARUH SELF-CONTROL, FINANCIAL SELF-EFFICACY DAN FINANCIAL KNOWLEDGE TERHADAP PENGELOLAAN KEUANGAN PRIBADI DENGAN GAYA HIDUP SEBAGAI VARIABEL MODERASI - Tegar Wahyu Hidayat; Dwi Puji Astuti (Jurnal Manajemen Pendidikan, 2026)
This study aims to examine the effects of self-control, financial self-efficacy, and financial knowledge on personal financial management, with lifestyle serving as a moderating variable among students of the Economics Education Study Program, Faculty of Economics and Business, Universitas Negeri Semarang, Class of 2022. This study employed a quantitative approach using a survey method. Data were collected through a four-point Likert-scale questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings indicate that self-control, financial self-efficacy, and financial knowledge have positive and significant effects on personal financial management. Furthermore, lifestyle strengthens the effect of financial self-efficacy on personal financial management but does not moderate the relationships between self-control and personal financial management or between financial knowledge and personal financial management. The findings also imply that improving self-control, confidence in financial management, and financial knowledge is essential for enhancing students' personal financial management. The novelty of this study lies in demonstrating that lifestyle plays a selective moderating role by strengthening only the relationship between financial self-efficacy and personal financial management, while it does not moderate the relationships involving self-control or financial knowledge.